Fatty Acid Methyl Ester Composition of Some Turkish Apiaceae Seed Oils: New Sources for Petroselinic Acid - Kucukboyaci, Nurgun; Ayaz, Fatma; Adiguzel, Nezaket; Bani, Baris; Goren, Ahmet Ceyhan (SAGE Publications, 2016)
The seed oils of twenty-six species of Apiaceae belonging to the genera Bunium, Cnidium, Ferula, Ferulago, Heracleum, Hippomarathrum, Malabaila, Myrrhoides, Olymposciadium, Pimpinella, Prangos, Szovitsia, Trigonasciadium, Trinia and Zosima, collected in Turkey, were investigated for their oil content, and amount of petroselinic acid (PA), as well as for the composition of their fatty acid methyl esters (FAMEs) by GC-MS. Seed oil content ranged from 7.1% in Szovitsia callicarpa to 29.3% in Ferula haussknechtii. The results showed that the seed oils of the studied species contained high amounts of PA (1.2–72.2%), followed by significant amounts of linoleic (LA, 13.8–50.8%) and oleic (OA, 4.2–61.6%) acids. PA was found in all the analyzed species, except for Olymposciadium caespitosum, which belongs to a monotypic endemic genus of the family. According to data from our study, PA was found to be predominantly in the seed oils of Hippomarathrum cristatum (72.2%), Trinia glauca (64.9%) and Bunium microcarpum (59.7%) and, therefore these species might be considered as new sources of PA, and represent a potential oleochemical raw material. This is the first extensive study of the composition of Turkish Apiaceae species. The high amounts of PA may also have chemotaxonomic significance.